Colony-forming endothelial cells – candidate culture for tissue vascular engineering: the gene and proteomic profile - M. Yu. Khanova; A. G. Kutikhin; V. G. Matveeva; E. A. Velikanova; E. O. Krivkina; L. V. Antonova (Фундаментальная и клиническая медицина, 2024)
Aim. To validate ECFC culture as a candidate culture for vascular tissue engineering using comparative analysis of the proteomic and gene expression profiles in comparison with cultures of human umbilical vein endothelial cells (HUVEC) and human coronary artery endothelial cells (HCAEC).Materials and Methods. ECFC culture was obtained by cultivating peripheral blood mononuclear cells of patients with coronary artery disease. Commercial HCAECs produced by Cell Applications, and HUVECs cultured according to the modified protocol of Jaffe were used as controls.The cells were lysed with TRIzol, and total RNA was isolated using a Purelink RNA Micro Scale Kit with concomitant DNase treatment. Next, rRNA depletion was carried out, followed by the creation of DNA libraries. DNA libraries were quantified using quantitative polymerase chain reaction on a CFX96 Touch Bio-Rad amplifier. DNA libraries were equimolarly mixed and sequenced on HiSeq 2000 (Illumina) with a paired-end reads of 2x125 nucleotides.Conventional western blotting was performed using pan-endothelial markers CD31, vWF, VEG-FR2/KDR, marker of endothelial progenitor cells CD34, markers of epithelial-mesenchymal transition Snail and Slug, and markers of endothelial specification: arterial HEY2, venous COUP-TFII and lymphatic LYVE1, VEGFR2. Dot blotting against 55 angiogenesis-related proteins was performed using Proteome Profiler Human Angiogenesis Array Kit in accordance with the manufacturer's protocol.Results. ECFC overexpresses markers of all three endothelial lineages (KDR, VWF, CD34, NRP2, FLT4 and LYVE1 compared to HCAEC; NOTCH4, DLL2) and LYVE1 compared to HUVEC. Proteomic profiling indicated ECFC as an intermediate population between HCAEC and HU-VEC in term of the expression of HEY2, LYVE1, VEGFR3, Snail and Slug. 261 DEGs were detected between ECFC and HUVEC, and 470 DEGs between ECFC and HCAEC.Conclusion. The gene expression profile of endothelial colony-forming cells corresponds to mature endothelial cells and indicates ECFC as an intermediate population between HCAEC and HUVEC. ECFC culture can be recommended for tissue vascular engineering.